Prepotency in rubber : Half-sib progeny evaluation - Mydin; Sankariammal L; Saraswathyamma C K; Thomas Vinoth (Proceedings of the 15th Plantation Crops Symposium, PLACROSYM XV, 10-13 December 2002, Mysore .pp.47-52.)
Rubber (Hevea brasiliensis Willd ex Adr.de Juss. Muell. Arg) is perennial out breeding species in which polycross breeding is effected by means of isolated sed gardens. Prepotent clones for use as seed garden components were identified by half sib progeny analysis of 11 clones recommended for planting in India. The two year old progenies showed significant variation for test tap yield, girth and bark thickness. Superior progenies were identified by a performance index based on yield, girth, bark thickness and number of latex vessel rows. Assigning index scores for the same traits, the recovery of superior seedlings within each progeny was worked out. The recovery of elite seedlings for cloning and further evaluation was also determined. Out of the eleven clones evaluated, five clones viz. PB 255, RRII 203, RRII 105, PB 260 and GT-1 were identified as likely prepotents with a high performance index and a higher recovery of superior and elite seedlings in their progeny.
Keywords: Half-sib progeny; Prepotency; Rubber